Ethical concerns associated with artificial intelligence in the accounting profession: a curse or a blessing? - Fülöp, Melinda Timea; Topor, Dan Ioan; Ionescu, Constantin Aurelian; Cifuentes-Faura, Javier; Măgdaș, Nicolae (Journal of Business Economics and Management, 2023)
Due to the progress of digitization and the associated use of artificial intelligence in the economic and especially the accounting field, the cooperation between man and machine is becoming increasingly prominent in society. The objective of this research to address the ethics of using artificial intelligence in the accounting firms by looking at the novel challenges that it brings to the field. The research adopted a deductive approach, starting with the basic concepts and then conducting an empirical study based on an interview. The results of the interview were processed with the Nvivo12 application, through which a thematic analysis was carried out in order to present the results. The research results indicate that most of the accountants involved in the study have a basic knowledge of artificial intelligence but that few of them fully understand the phenomenon. However, they all believe that the ethics of artificial intelligence is vital and that the involvement of regulatory bodies in ethical legislation regarding artificial intelligence is indispensable. The results obtained can serve as an X-ray of the current situation and can be used to derive practical and managerial implications.